Analysis of Opportunities and Challenges for Podcasts as a Means of Islamic Preaching in the Digital Era - Izzudin Hitimala (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This research investigates the opportunities and challenges associated with using podcasts as a means of proselytizing in the digital age. The aim is to understand the potential of podcasts in reaching a wider audience, the flexibility of production, and the interaction provided to the audience. In addition, this research also aims to identify challenges such as intense competition, resource-intensive production, regulation, and potential negative impacts. The research method used is library research to analyze various literature sources with in-depth analysis to unravel the formulation of the research problem. The results of this study reveal that podcasts have great potential in spreading religious and moral messages to geographically diverse audiences. The flexibility of production and interaction with the audience are also positive aspects. However, the proselytizing community needs to overcome fierce competition and ensure adequate production quality. Applicable regulations must be understood, and proselytizers must communicate carefully to avoid negative impacts. In order to utilize the potential of podcasts as an effective da'wah tool, careful content planning, strong promotion, in-depth understanding of regulations, and monitoring of technological trends are key in facing the challenges. Podcasts can be a powerful means of da'wah in this digital era if managed properly and wisely.